Neologizmy i nowe formacje. Słowotwórstwo w dydaktyce języka włoskiego w Polsce: obserwacje i wyzwania - Kozakiewicz-Kłosowska, Dorota (Neofilolog, 2026)
The article discusses the difficulties associated with teaching and learning new Italian vocabulary as a foreign language in the Polish context. The research material includes lexical data from contemporary Italian language observatories and the results of two surveys: one conducted in 2025 among students and lecturers at Italian universities, and the other concerning the needs of Italian learners at the Faculty of Applied Linguistics, University of Warsaw. The article emphasizes the importance of creative word formation and mediation skills as key elements in teaching Italian vocabulary in the context of new multilingualism, in which neologisms and resemantizations function as communication and cultural tools. The considerations present the process of language learning as dynamic and requiring going beyond the framework of textbooks. The conclusions presented include proposals for solutions supporting language teaching that is sensitive to the complexity of contemporary contrastive communication.